Fibrin Clot Augmentation During All-Inside Meniscal Repair: Pull-In Technique - Amit Joshi, M.S.(Ortho); Rohit Bista, M.S.(Ortho); Umair Ahmad, F.C.P.S.(Ortho); Hiramani Paudyal, M.S.(Ortho); Alok Thaiba, M.S.(Ortho); Rajiv Sharma, M.S.(Ortho) (Arthroscopy Techniques)
Various augmentation techniques have been described to improve the biological environment after meniscal repair, especially meniscal repairs in which the anterior cruciate ligament is intact. Fibrin clot augmentation is preferred because of its cost-effectiveness and favorable outcomes. Accurate clot placement at the tear site and stability during the repair are crucial for fibrin clot augmentation. Various techniques are described in the literature, but most are limited to a particular type of meniscal repair or are technically challenging. We describe a simple, reproducible technique of delivering the clot to the tear site that can be implemented during all types of meniscal repair and keeps the fibrin clot at the tear site during the meniscal repair process.